Evaluasi Proses Pelaksanaan Pembelajaran Daring Kelas II di SDN Sudimara 12 Ciledug Tangerang - Anisa Wiji Astuti; Septy Nurfadhillah; Sa’odah Sa’odah (RC-INSTITUT, 2021)
This study is intended to evaluate the process of implementing online learning (in the network) at SDN Sudimara 12 Ciledug, Tangerang city. This evaluation is focused on how the learning implementation process takes place. Existing learning planning and the difficulties that exist when online learning takes place. The purpose of this study was to obtain information about how the implementation process during online learning was carried out. This study used qualitative research with the phenomenological method. At SDN Sudimara 12 Ciledug, Tangerang city, the respondents were second grade teachers and a sample of 8 students. The research data were collected using interviews, observation and documentation. Based on the results of the study, the evaluation of the process of implementing online learning at SDN Sudimara 12 has been going well.